India – Canada Relations Post-Cold War Perspective – Part 2 - Majumdar, Ananda (European Journal of Multidisciplinary Studies, 2018)
From the perspective of this great relations, the purpose of this essay is to explore a dynamic amalgamation between two great democracies on the basis of education, culture, economy, defense, social phenomena, it is a broad-based story since India’s independence to at present through which a relation between India and Canada has been settled on a true nature through various ways of cooperation, contribution, support, aid and many more. I am in Canada and as a student and researcher. I would like to approach this relation more fruitful and cordial by its nature. I would like to pursue my study in International Development and topic like this will be helpful for me to explore ideas, presentation, proposal writing, and developments between countries which is useful for the development of human being. This topic is my academic thesis during my master’s program in International Relations at Jadavpur University, Kolkata, West Bengal, India.